Zakat and Empowerment of the Bajo Tribe Fishing Community in Bone, South Sulawesi: Collaboration between BAZNAS and the Ministry of Religion - Husain, Hukmiah; Said, Wardana; Darwis, Muh.; Arafah, Muh.; Hasan, Hamsah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Bajo tribe is a traditional fishing community in Bone Regency, South Sulawesi, which faces the challenge of persistent poverty in various aspects. The National Zakat Amil Agency (BAZNAS) in collaboration with the Ministry of Religion has taken important steps to empower this community through educational values-based programs. This research aims to analyze the role of collaboration between BAZNAS and KUA in efforts to empower the coastal communities of the Bajo Tribe through the utilization of zakat. This research uses empirical legal methods using empowerment theory. Community development and empowerment aims to change community conditions for the better, in educational, economic, social, cultural and political aspects. Data was collected by means of in-depth interviews with BAZNAS, KUA, and the Bajo tribal community, while literature studies referred to relevant articles, books and research reports. The research results show that the collaboration between BAZNAS and KUA has contributed to changing the mindset of the Bajo Tribe in educating the Bajo Tribe community so that they improve spiritually, health and religious education. The challenges faced are the lack of realization of more massive program sustainability and the lack of active involvement of the community, stakeholders and the importance of realizing community empowerment through zakat environmental development in accordance with the BAZNAS RI program which is intended for community groups who experience economic, educational, health, spiritual and economic disadvantage welfare. Even though the results are not optimal, this contribution should be appreciated because it has had a significant impact on empowering the Bajo ethnic community on the Bone coast of South Sulawesi.